TRUCK BEHAVIOR AS AUTONOMOUS AGENT IN SAFETY SIMUALTION GAME AT FUEL DISTRIBUTION DEPOT - DARU KUSUMA (NIM: 23207146), PURBA
Fuel truck has an important role in Safety Simulation Game at Fuel Distribution Depot. Fuel Truck roles as an agent on duty in the transport of fuel from the depot to be carried out of the depot. During his time in the depot, the fuel truck has some activities. Activities are run in accordance with certain rules. On the other hand, the fuel truck as autonomous agent which its behavior is determined by the character itself. Thus, the behavior of the truck with the other is not always the same. This research is expected to contribute to enrich the vehicle behavior algorithm as an autonomous agent of the role in running the vehicle in the environment. This research is expected to provide an understanding of aspects that build the behavior of the truck, the relationship between the aspects, and aspects scoring in the form of vehicle. This research is conducted based on some initial theories that underlie behavior trucks. A* algorithm is selected to build a vehicle pathfinding procedure. Kinematic tricycle theory is used to determine the movement position and rotation of vehicle. Reciprocating engine and gear ratio theory is used to determine vehicle speed. Myer-Briggs Type Indicator model is used to build a psychological model of truck driver. This research is carried out by learning the basic concept of the movement of moving objects in the example program in Direct3D games, analyzing gaps in the basic concept of the movement of objects moving in the example program in Direct3D games, and further modifying the basic concept of the movement of objects that already exist with the model of behavior that was built in this research. Development of the model behavior of the truck is done through several stages. The first stage is preparing the model of finite state machine (FSM) of the truck. The second phase is to collecting and scoring factors that forms behavior of the truck. Third stage is determining the calculation formula of the derivative factors. Fourth stage is the designing flowcharts of the truck. Fifth stage is the implementing the model into source code. Sixth stage is testing the model of the truck. This research has produced behavior model of truck at the fuel distribution depot. This model can be an alternative model of vehicle. Model that is produced in this research can still continue to be developed into a more complex vehicle behavior model.